Enhancing Maternal Health: IT Solutions for Monitoring Anemia in Pregnancy - Novy Ernawati; Muhamad Rizki; Rosmiati Rosmiati; Oktavirona Oktavirona (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
Background: Anemia is a condition in which a deficiencyof red blood cells (erythrocytes) in the blood cycle or mass of hemoglobin is so unable to fulfill its function as a carrier of oxygen in the entire tissue. Handling to increase hemoglobin levels by using pharmacological and non-pharmacological management, one of the non-pharmacological management is by giving vitamin C so that the process of absorption and formation of hemoglobin is faster such as consuming red guava juice every day 2 x 1 together with Fe. the study was to determine the effect of giving Fe tablets and red guava juice on increasing hemoglobin levels in third trimester pregnant women. This pre-post experimental research design uses a design pretest-posttest whit control group design. The sampel in this study 36 respondents consisting of 18 experimental respondents and 18 control respondents with purposive sampling technique. The research instrument used the measuremets tool HB Family Dr. Test Strip and observation for 2 weeks. Data were analyzed using paired t-test to determine changes before and after and independent T-Test to determine the difference between the experimental group and the control group. The results of the pre-post study in the experimental group were p values of 0,000(p <0.05) and in the control group were 0.01(p <0,05). The results of the pre-post study in the experimental and control group p value 0,000. There is an effect of giving red guava juice and Fe tablets to increase hemoglobin levels of pregnant women in the third trimester who have mild anemia. Therefore, it is hoped that PMB (Praktek Mandiri Midwives) can pay attention to the handling of anemia in pregnant women in Kedaung, Pamulang, Tangerang. South with outreach programs and supplementation such as giving red guava juice.